Comprehensive GaN-on-Si power device platform: epitaxy, device, reliability and application. (4th May 2021) - Wong, Roy K-Y; Hao, Ronghui; Chou, Allen; Zou, Y B; Shen, J Y; Li, Sichao; Yang, C; Hu, Tiger; Chen, F; Zhang, J H; Zhang, Ray; Cao, Kenny; et al.
Abstract: In this paper, we discuss possible solutions to overcome the critical issues for GaN-on-Si power device popularization including cost competitiveness to Si power MOSFETs, system level reliability verification, and electromagnetic interference (EMI) mitigation at high switching frequency without compromising the switching loss. Both an advanced epitaxy technology and a comprehensive power device technology platform of 200 mm GaN-on-Si high electron mobility transistors (HEMTs) for mass production are presented. A novel strain engineering is reported to realize enhancement-mode HEMTs with ultralow specific on-resistance. The Si based Joint Electron Device Engineering Council reliability test, Dynamic High Temperature Operating Life, and switching accelerated lifetime test were carried out to evaluate the device reliability and lifetime. It is proved that our GaN device is robust and stable in power conversion applications. A balancing technique to mitigate EMI of the high switching frequency GaN power converter is demonstrated.